Fast crustal deformation computing method for multiple computations accelerated by a graphics processing unit cluster. Issue 2 (10th May 2017) - Yamaguchi, Takuma; Ichimura, Tsuyoshi; Yagi, Yuji; Agata, Ryoichiro; Hori, Takane; Hori, Muneo
Abstract: As high-resolution observational data become more common, the demand for numerical simulations of crustal deformation using 3-D high-fidelity modelling is increasing. To increase the efficiency of performing numerical simulations with high computation costs, we developed a fast solver using heterogeneous computing, with graphics processing units (GPUs) and central processing units, and then used the solver in crustal deformation computations. The solver was based on an iterative solver and was devised so that a large proportion of the computation was calculated more quickly using GPUs. To confirm the utility of the proposed solver, we demonstrated a numerical simulation of the coseismic slip distribution estimation, which requires 360 000 crustal deformation computations with 82 196 106 degrees of freedom.